Interactions Between Fe(III)-Oxides and Fe(III)-Phyllosilicates During Microbial Reduction 1: Synthetic Sediments. Issue 9 (20th October 2016) - Wu, Tao; Kukkadapu, Ravi K.; Griffin, Aron M.; Gorski, Christopher A.; Konishi, Hiromi; Xu, Huifang; Roden, Eric E.
ABSTRACT: Fe(III)-oxides and Fe(III)-bearing phyllosilicates are the two major iron sources utilized as electron acceptors by dissimilatory iron-reducing bacteria (DIRB) in anoxic soils and sediments. Although there have been many studies on microbial Fe(III)-oxide and Fe(III)-phyllosilicate reduction with both natural and specimen materials, no controlled experimental information is available on the interaction between these two phases when both are available for microbial reduction. In this study, the model DIRB Geobacter sulfurreducens was used to examine the pathways of Fe(III) reduction in Fe(III)-oxide stripped subsurface sediment that was coated with different amounts of synthetic high surface area (HSA) goethite. Cryogenic (12K) 57 Fe Mössbauer spectroscopy was used to determine changes in the relative abundances of Fe(III)-oxide, Fe(III)-phyllosilicate, and phyllosilicate-associated Fe(II) [Fe(II)-phyllosilicate] in bioreduced samples. Analogous Mössbauer analyses were performed on samples from abiotic Fe(II) sorption experiments in which sediments were exposed to a quantity of exogenous soluble Fe(II) (FeCl2 ⋅2H2 O) comparable to the amount of Fe(II) produced during microbial reduction. A Fe partitioning model was developed to analyze the fate of Fe(II) and assess the potential for abiotic Fe(II)-catalyzed reduction of Fe(III)-phyllosilicates. The microbial reduction experiments indicated that although reduction of Fe(III)-oxide accounted for virtually all of the observed bulk Fe(III) reduction activity, there was no significant abiotic electron transfer between oxide-derived Fe(II) and Fe(III)-phyllosilicatesilicates, with 26–87% of biogenic Fe(II) appearing as sorbed Fe(II) in the Fe(II)-phyllosilicate pool. In contrast, the abiotic Fe(II) sorption experiments showed that 41 and 24% of the added Fe(II) engaged in electron transfer to Fe(III)-phyllosilicate surfaces in synthetic goethite-coated and uncoated sediment. Differences in the rate of Fe(II) addition and system redox potential may account for the microbial and abiotic reaction systems. Our experiments provide new insight into pathways for Fe(III) reduction in mixed Fe(III)-oxide/Fe(III)-phyllosilicate assemblages, and provide key mechanistic insight for interpreting microbial reduction experiments and field data from complex natural soils and sediments.